Magnetic nanostructures for marine and freshwater toxins removal. (October 2020) - González-Jartín, Jesús M.; de Castro Alves, Lisandra; Alfonso, Amparo; Piñeiro, Y.; Vilar, Susana Yáñez; Rodríguez, Inés; Gomez, Manuel González; Osorio, Zulema Vargas; Sainz, María J.; Vieytes, Mercedes R.; Rivas, J.; Botana, Luis M.
Abstract: Marine and freshwater toxins contaminate water resources, shellfish and aquaculture products, causing a broad range of toxic effects in humans and animals. Different core-shell nanoparticles were tested as a new sorbent for removing marine and freshwater toxins from liquid media. Water solutions were contaminated with 20 μg/L of marine toxins and up to 50 μg/L of freshwater toxins and subsequently treated with 250 or 125 mg/L of nanoparticles. Under these conditions, carbon nanoparticles removed around 70% of saxitoxins, spirolides, and azaspiracids, and up to 38% of diarrheic shellfish poisoning toxins. In the case of freshwater toxins, the 85% of microcystin LR was eliminated; other cyclic peptide toxins were also removed in a high percentage. Marine toxins were adsorbed in the first 5 min of contact, while for freshwater toxins it was necessary 60 min to reach the maximum adsorption. Toxins were recovered by extraction from nanoparticles with different solvents. Gymnodinium catenatum, Prorocentrum lima, and Microcystis aeruginosa cultures were employed to test the ability of nanoparticles to adsorb toxins in a real environment, and the same efficacy to remove toxins was observed in these conditions. These results suggest the possibility of using the nanotechnology in the treatment of contaminated water or in chemical analysis applications. Highlights: A new green methodology to remove phycotoxins and cyanotoxins was developed. The efficacy of 2 magnetic nanoparticles as toxin adsorbents was tested. Nanoparticles allow to remove up to 70% of certain phycotoxins. Nanoparticles allow to remove up to 85% of certain cyanotoxins. Toxins can be recovered by extracting nanoparticles with different solvents.